Where there’s brass. (Economist, 2017)
The article discusses the U.S. President-elect Donald Trump's invective against the U.S. mass media and against the U.S. intelligence service concerning allegations that Russia has compromising information about him. The U.S. intelligence service's report that Russia was involved in hacking to influence the U.S. 2016 presidential election is discussed.